Islam in the World Today: A Handbook of Politics, Religion, Culture, and Society - Ende, Werner; Steinbach, Udo (Cornell University Press, 2010)
Considered the most authoritative single-volume reference work on Islam in the contemporary world, the German-language Der Islam in der Gegenwart, currently in its fifth edition, offers a wealth of authoritative information on the religious, political, social, and cultural life of Islamic nations and of Islamic immigrant communities elsewhere. Now, Cornell University Press is making this invaluable resource accessible to English-language readers.More current than the latest German edition on which it is based, Islam in the World Today covers a comprehensive array of topics in concise essays by some of the world's leading experts on Islam, including:• the history of Islam from the earliest years through the twentieth century, with particular attention to Sunni and Shi'i Islam and Islamic revival movements during the last three centuries;• data on the advance of Islam along with current population statistics;• Muslim ideas on modern economics, on social order, and on attempts to modernize Islamic law (shari'a) and apply it in contemporary Muslim societies;• Islam in diaspora, especially the situation in Europe and America;• secularism, democracy, and human rights; and• women in Islam Twenty-four essays are each devoted to a specific Muslim country or a country with significant Muslim minorities, spanning Asia, Africa, the Middle East, and the former Soviet Union.Additional essays illuminate Islamic culture, exploring local traditions; the languages and dialects of Muslim peoples; and art, architecture, and literature. Detailed bibliographies and indexes ensure the book's usefulness as a reference work.
Keywords: Geschichte 1800-2010; Kunst; Kultur; Gesellschaft; Politik; Islam; Europa; Afrika; Asien